ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI DI INDONESIA TAHUN 1990 – 2017 - Rauzatul Jannah; Asnawi Asnawi (Jurnal Ekonomi Regional Unimal, 2019)
This study aims to analyze the influence of interest rates, inflation, exchange rates and economic growth on investment in Indonesia from 1990 to 2017. The data used in this study are secondary data obtained from www.bps.go.id and www.bi.go. id. The data analysis method used is multiple linear regression. The results show that interest rates have a negative and significant effect on investment in Indonesia, Inflation has no effect on investment in Indonesia, Exchange rates have a positive and significant effect on investment in Indonesia, Economic growth has a negative and significant effect on investment in Indonesia. Simultaneously, interest rates, inflation, exchange rates and economic growth influence investment in Indonesia.